The role of pelagic-benthic coupling in structuring littoral benthic communities at Terra Nova Bay (Ross Sea) and in the Straits of Magellan - CATTANEO VIETTI R.; CHIANTORE, MARIACHIARA; MISIC, CRISTINA; POVERO, PAOLO; FABIANO, MAURO (Instituto de Ciencias del Mar:Pas Maritim Barceloneta 37-49, 08003 Barcelona Spain:011 34 93 2309500, EMAIL: scimar@icm.csic.es, INTERNET: http://www.icm.csic.es/sm.html, Fax: 011 34 93 2309555, 1999)
In Antarctic and peri-Antarctic regions, benthic communities are persistentìn time and sh-ow high biomass and large numbers of individuàls, mainly consiiting of suspension and deposit feeders. In fact, apart from recluitment, the majór factor structuring these communities is the high flbw of organic matler from the pelagic. domain to the bottom, represónting an important énergy source for the benthicìrganisms. The aimof this pape_r-i9to review, compile and compaie the daìà from earlier inveJtigations in Terra Nova Bay (Ross Sea) and the Straits of Magellan, in order to come to a 'more general conclusion about the role of the pelagic-bénthic coupling in_ sÍucturing littoral benthic communities in southein coastal areas. Few measurements of flux rates and the biochemical composition of the sinking particles occurring in Antarctic and peri-Antarctic shallow waters are available, but a compilation of our own dala. and others al1ows a coÀoarison of these tiro svstems. The different environmental conditions bètween Antarctica and the Straits of Magellan lèad to differences in the origin of the particulate organic matter and in its biochemical composition, and consequently in the coupling between pelagió and benthic domains. At Terra Nova Bay the summer particulate matter shows a high iabile fraciion-of a good food-value: its flux has been evaluated at about 0.67 g m'2dr. Conversely, the Straits,of Magellan show multi-strùctured ecosystems where the quality and quantity of the organic matter flux. towards the bottom change according to the local geomorphology and^currént dynàmics. Moreover, the three-dimensional assemblages,of suspànsion-feedels, so commo-n in Antarctic shallow wateri, seem to be absent in the Magellan area. In g1{i9ula1 sponges, gorgonanans and bryozoans play a secondary role inside the Straits ofMagellan, where.polychaetes (60%) and motlùscs (O-I07o) are dominant on sofî bóttoms, and where they reach high values in density and biomass. Bivalves seem to play an important roie in both regions: for ...